Analysing The Influence Of Organaizational Culture, Felt Leadership And Company Compensation On Employee Performance: Astudy Of PT XYZ - Dudi Komaruddin; Tien Yustini; Jefirstson R.Riwu Kore Jefritson@uigm.ac.id (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of organizational culture, felt leadership and compensation on PT XYZ employee performance in MUBA Regency, South Sumatra. Descriptive research uses a quantitative approach method by measuring organizational culture, felt leadership and compensation for PT XYZ workers. Data collected by distributing questionnaires and designing analysis using the SPSS program. Population of study was 100 people, all of whom were research samples. Research results show regarding worker performance; organizational culture has a negative effect with tcount (-3.527) < ttable (0.1984), felt leadership has a positive effect with tcount (6.801) > ttable (0.1984), and compensation has a positive effect with tcount (3.753) > ttable (0.1984). These three independent variables simultaneously influence worker performance with Fcount (31.919) > Ftable (2.70), with influence size of 59.2%, while remaining 40.8% of worker performance can be explained by other variables not studied, such as work’s motivation, discipline, competence and work environment.